Analysis and design of microwave bandpass filters and amplifiers - Tan, Johin Chia Yong. (2011)
This project examines the frequency response during the designing and fabricating of Microwave Parallel Coupled Line Bandpass Filter and Reflective Match BJT Amplifier. Design theories for microstrip and both microwave devices were covered in order to have a clear understanding of the design procedures and essential formulas. Through this project, an Advance Design System (ADS) software was used to design and achieve simulated results for comparison with the actual fabricated product. A total of five filters and five amplifiers were designed and fabricated with their processes elaborated and findings evaluated explicitly in this report. With the enhancements of each trial design discussed and implemented, two successful bandpass filters and a transistor amplifier were produced ultimately.